Identifying Malnutrition Risk Factors In Vulnerable Groups: A Fundamental Approach To Implementing Complementary Therapy In Health Crisis Mitigation - Muflih, Muflih; Widaryanti, Rahayu; Erwanto, Rizky (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Malnutrition is a pressing global health issue affecting vulnerable communities, including children and elderly populations. This research aimed to identify the risk factors associated with malnutrition in these groups and explore the potential of complementary therapy in mitigating health crises caused by malnutrition. A comprehensive survey was conducted, collecting data from diverse vulnerable communities. The survey design included structured questionnaires, open-ended questions, and focus group discussions to gather quantitative and qualitative data. The findings revealed that food insecurity, limited access to healthcare, low socio-economic status, insufficient dietary diversity, and inadequate micronutrient intake were significant risk factors contributing to malnutrition. Moreover, participants expressed positive perspectives on the potential efficacy of complementary therapy in nutrition support and emphasized the importance of community engagement and integration with existing healthcare systems. The study concludes that evidence-based strategies and targeted interventions are crucial to address malnutrition and improve the health outcomes of vulnerable populations. The research findings contribute to a better understanding of malnutrition and lay the groundwork for sustainable solutions to mitigate health crises related to malnutrition.